Gynecomastia Treatment by Liposuction with Gland Excision and H.H. Method - Haider Ali Muslim AL Ramahi (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Gynecomastia (GM) is benign enlargement of male beast (glandular enlargement with fat accumulation). we classify in 6 grades depend on size and shape of breast. All cases were treated surgically as combine of gland excision and liposuction and added new method HH (Haider and Husam) method which is specific for grade 5 and 6 GM.Method: From 2013 to 2018, a chart review was performed for 300 patients. Preoperative examination included endocrine and urological examination and exclusion of other pathological conditions. The surgical technique consisted of liposuction through small incision in lateral side of breast, combine with gland excision by sub areolar incision and sometime HH method depend on grade of gynecomastia.Results: Total number of patient 300 cases all of them under want combination of liposuction and gland excision with drain keep for about 8 hours. Recurrent rate very rare and complication like infection or areolar necrosis also rare and 9 case only suffering from early postoperative bleeding and 22 cases develop seroma within 2 weeks.Conclusions: This analysis data that include treatment of GM grade 1-6 is performed by liposuction combined with subcutaneous resection of the glandular tissue by sub areolar incision the procedure had low rate of complications and excellent patients’ satisfaction about the results. Preoperative fellow up is important to rule out and prevent specific complication of procedure and to exclude diseases or malignancy causing the GM as all gland sent to histopathology